Performance Evaluation of Conventional and High Modulus Asphalt Concrete with Novolac Polymer Modifier Using Aashtoware Software - H. Al-Humeidawi, Basim; F. Jasim, Abbas; A. Kadhim, Huda (International Journal of Engineering and Technology, 2018)
In order to changes the original asphalt characteristics, there are many additives have been used to produce or modify the High Modulus Asphalt Binder (HMAB). Even though the hard grade asphalt binder has some disadvantages, such as the aging process due to high mixing and compacting temperature, which can negatively affect the pavement performance, some other advantages include increasing stiffness modulus of asphalt binder and high resistance to permanent deformation. Also, using the hard grade asphalt binder will save construction costs by reducing the asphalt pavement thickness due to its high stiffness modulus. In Iraq, the Novolac modifier and its Cross-linking Agent (Hexamine) was used for the first time as a modifier for asphalt which can significantly improve the rheological properties of asphalt and its role in HMA. This study focuses on estimating the thickness reduction of flexible pavement due to using High Modulus Asphalt Concrete (HMAC). The reduction in permanent deformation and thickness of pavement were estimated for suggested pavement structure sections implemented HMAC mixture compared with the pavement section implemented conventional mixtures using AASHTOWare software version 2.3. The analytical results indicate that adding 4% of Novolac modifier and 15 % of Hexamine (form weigth of Novolac) is reduced the permanent deformation and bottom up cracking by 30% and 46 % compared to conventional mix, respectively. However, it can be concluded that adding Novolac polymer modifier enhanced the pavement performance.Â Â